The Place of Information and Communication Technology in the Effective Teaching and Learning of History in the Nigerian Educational Institutions In The 21st Century - Adesola Samson Adesote (Unib Press, 2022)
The main thrust of this paper is to critically examine the place of Information and Communication Technology (ICT) in the effective Teaching and Learning of History in the Nigerian institutions in the 21st century. It argues that the new Information and communication technologies of internet and multimedia which have led to positive impact in the field of education in most developed countries are still at infancy or not used at all in the classroom instruction in most developing countries (Nigeria inclusive). ICTs are potential powerful enabling tools for effective teaching and learning in educational institutions. Thus, the paper argues that the central role of ICT is to provide additional strategies that can be used to address major educational challenges being faced by teachers and students of History Nigerian educational institutions in the 21st century. The paper, therefore, concludes that the appropriate use of ICTs can positively influence and change traditional methods of teaching and learning of History in Nigerian educational institutions, thereby making the teaching and learning of History more concrete. The methodology adopted in this paper is qualitative and analytical utilizing materials from the primary and secondary sources